Failure Characteristics and Confined Permeability of an Inclined Coal Seam Floor in Fluid-Solid Coupling - Jian Sun; Lianguo Wang; Guangming Zhao (Advances in Civil Engineering)
Secondary development of FLAC3D software was carried out based on FISH language, and a 3D fluid-solid coupling numerical calculation model was established for an inclined seam mining above a confined aquifer in Taoyuan Coal Mine. A simulation study was implemented on the mining failure depth of an inclined coal seam floor, conducting height of confined water, and the position of workface floor with easy water inrush during advancement of workface. Results indicated that, during the advancement of the inclined coal seam’s workface, obvious equivalent stress concentration areas existed in the floor strata, and the largest equivalent stress concentration area was located at the low region of workface floor. When the inclined coal seam workface advanced to about 80 m, the depth of floor plastic failure zone reached the maximum at approximately 15.0 m, and the maximum failure depth was located at the low region of the workface floor. Before the inclined workface mining, original confined water conducting existed on the top interface of the confined aquifer. The conducting height of the confined water reached the maximum at about 11.0 m when the workface was pushed forward from an open-off cut at about 80 m. Owing to the barrier effect of the “soft-hard-soft” compound water-resistant strata of the workface floor, pore water pressure and its seepage velocity in the floor strata were unchanged after the workface advanced to about 80 m. After the strata parameters at the workface floor were changed, pore water pressure of the confined water could pass through the lower region of the inclined workface floor strata and break through the barrier of the “soft-hard-soft” compound water-resistant strata of the workface floor and into the mining workface, resulting in the inclined coal seam floor water inrush. Results of this study can provide a basis for predicting, preventing, and governing the inclined coal seam floor water inrush above confined aquifer.